The Functional Outcome of Mini Carpal Tunnel Release - Anbarasan, Amaleswaran; Thevarajah, Nahulan; Sadagatullah, Abdul Nawfar (Journal of Hand and Microsurgery, 2017)
Introduction Carpal tunnel syndrome (CTS) is one of the most common compression neuropathies in the upper limbs and requires surgery if conservative treatment fails. This study assessed the functional outcome of vertical mini carpal tunnel release (CTR) at distal wrist crease.Objective To evaluate prospectively the safety, effectiveness, and reproducibility of vertical mini-open blind technique for CTR.Methods In total, 36 patients (40 hands) aged between 22 and 71 years with mild to moderate CTS based on nerve conduction studies were selected and screened based on inclusion and exclusion criteria. The surgery was done with vertical mini-incision CTR at distal wrist crease. The preoperative and postoperative clinical outcomes and grip strength were evaluated with Levine–Katz questionnaire and JAMAR Hydraulic Hand Dynamometer with 3 months follow-up after surgery.Results The mean score for both symptom severity and functional status reduced and mean handgrip strength improved 29.5% at 3 months after surgery. All the patients were satisfied with the cosmetic outcome of the scar. Three patients had scar tenderness. All patients were able to return to work within 4 weeks after surgery, except one who developed chronic regional pain syndrome.Conclusion The vertical mini-open blind technique has been shown to be safe and easily reproducible and has short recovery period. All patients return to good functional status 3 months postoperative.
Keywords: carpal tunnel syndrome; mini carpal tunnel release; handgrip strength; Levine–Katz questionnaire